Economical evaluation of the living environment polution - CSIKÓSOVÁ, ADRIANA; KAMENÍKOVÁ, KATARÍNA (Boletim Paranaense de Geociências, 2002)
The present paper analyses a magnesite firm and its influence on the living environment due to air pollution, water pollution and soil pollution. The analysed firm is a producer of clinker and magnesite products that are exported to some big countries of the world. It is a lucrative firm with a profit achievement during the following period. But it must pay considerable fees for polluting the living environment and therefore it must accept several measures for improving ecological behaviour of the firm.